Analisis Kontrastif Modalitas Epistemik dan Deontik Nakerebanaranai, Beki dan Hazu dengan Harus dan Seharusnya - Diwana Fikri Aghniya, - (2021)
In Japanese there are many types of modalities. Among these modalities, there are epistemic modalities and deontic modalities. From these two types of modalities, there are several modalities that have similar meanings. Japanese language learners find it difficult to distinguish their use. These modalities are nakerebanananai, beki, and hazu in Japanese and 'harus' and 'seharusnya' in Indonesian. This study examines the similarities and differences between nakerebanaranai, beki, and hazu with 'harus' and 'seharusnya'. This research is a qualitative descriptive research. This research uses data from corpus, articles and online news. Data were collected by observation and writing methods. All of these data is divided into two types of modalities, analyzed by substitution method, then compared the similarities and differences through contrastive and semantic research methods. From the results of this study, it can be clearly seen the similarities and differences between nakerebanaranai, beki, and hazu with 'harus' and 'seharusnya'. There are 13 similarities and 2 differences between nakerebanaranai and harus. 9 similarities and 5 differences between nakerebanaranai and seharusnya. There are 8 similarities and 4 differences between beki and harus, 5 similarities and 8 differences between beki and seharusnya. There are 3 similarities and 11 differences between hazu and harus, 6 similarities and 9 differences between hazu and seharusnya.